Bimbingan Karir dalam Perencanaan Karir Remaja Akhir - Nurul Hidayati Ade; Marvel Maloti (Jurnal Bintang Pendidikan Indonesia, 2024)
Career guidance has an important role in helping late adolescents direct and plan their future, especially in determining an appropriate career path. Late teens are in an important transition phase from the world of education to the world of work, where they are faced with various career choices. Good career planning requires a thorough understanding of personal interests, talents and values ​​as well as the opportunities available in the world of work. Career guidance aims to provide insight and guidance to late teens regarding the right decision-making process regarding their careers. Through career guidance, teenagers can identify their strengths and weaknesses, understand the various professions available, and prepare themselves for challenges that may arise in the future. This guidance also functions to increase teenagers’ self-confidence in choosing a career path that suits their abilities and desires. Apart from that, teenagers are also taught to consider various factors such as economic conditions, job market needs, and technological changes that can influence career choices in the future. The literature study method was used in this research to explore various theories and approaches that are relevant in career guidance for late adolescents. By reviewing various existing literature, a deep understanding can be found about how career guidance can help young people plan and prepare for their future careers effectively. This literature study also provides an overview of the challenges and strategies that can be used in the career guidance process for late adolescents.